2019
DOI: 10.1007/s10570-019-02737-x
|View full text |Cite
|
Sign up to set email alerts
|

Wood protective coatings based on fluorocarbosilane

Abstract: The effectiveness of protective coatings based on 3- (2,2,3,3,4,4,5,5-octafluoropentyloxy)propyltriethoxysilane in the protection of wood surface from the effects of water was tested. No earlier attempts at using the mentioned fluorocarbosilane for the protection of wood have been reported in the literature. The coatings were deposited by the sol-gel method. As a result of the generation of chemical bonds between the wood surface and silane, a coating was produced that permanently increased the wood hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…It clearly shows that the paper treatment with starch modi ed with WR ensured the best hydrophobization of the material and improved the hygroscopic properties. Similar results on the effectiveness of uorosilane coating were reported bySzubert et al (2019), where high hydrophobic properties of surface treated wood were presented (WCA > 120°). The disparate characteristics obtained for the interaction of coated paper with moist air are presumably related to mechanisms blocking active sorption sites within the paper and/or starch.…”
supporting
confidence: 87%
“…It clearly shows that the paper treatment with starch modi ed with WR ensured the best hydrophobization of the material and improved the hygroscopic properties. Similar results on the effectiveness of uorosilane coating were reported bySzubert et al (2019), where high hydrophobic properties of surface treated wood were presented (WCA > 120°). The disparate characteristics obtained for the interaction of coated paper with moist air are presumably related to mechanisms blocking active sorption sites within the paper and/or starch.…”
supporting
confidence: 87%
“…To the best of our knowledge, research in this area has not provided a very extensive previous background and few studies or patents cover this field of interest [8][9][10][11][12]35].…”
Section: Treatments Evaluationmentioning
confidence: 99%
“…Impregnation of wood with silicon compounds improves its dimensional stability and resistance to weather conditions [18][19][20][21]. Kim et al (2011) [22] observed that silane treatment significantly improved tensile, flexural, and impact strength of polypropylene composites.…”
Section: Introductionmentioning
confidence: 99%